Penyuluhan Sosialisasi Pemanfaatan Buah Lerak sebagai Deterjen Alami Anti Sodium Lauryl Sulfate (SLS) di Desa Gunungsari - Muliasari, Zully Intan; Rosyada, Alfina; Addeny, Tirta Langgam; Amelia, Adinda Mella; K, Jacinda Luby Belvana; Rahmadiny, Yuan Septya; Rifkiyanto, Muhammad Naufal; Saputra, Muhammad Rizky Wahyu; Insani, Nailul (ALSYS, 2025)
This research aims to address the issue of environmental pollution caused by household waste, focusing on the community of Gunungsari Village, Batu. The study was conducted through community service activities and raising awareness about the impacts of environmental pollution and ways to mitigate it. The research utilized the Service-Learning methodology by providing information, knowledge, and understanding to the community to address a specific issue. Additionally, an outreach approach was implemented by directly introducing a new innovation—natural detergent made from soapberries (lerak fruit). The community was informed about soapberries, their benefits, and the processing methods to create a natural detergent free from Sodium Lauryl Sulfate (SLS), which could replace the conventional detergents previously used. The direct community engagement revealed that soapberries had been used by past generations but the knowledge had gradually faded over time as it was not preserved or passed down to subsequent generations. Therefore, it can be concluded that soapberries can indeed be utilized as a base ingredient for producing natural, SLS-free detergent. This innovation is expected to benefit the community.